Keanekaragaman Jenis Burung Pada Tiap Kelas Kerusakan Di Dalam dan Di Luar Taman Nasional Gunung Merapi Pasca Erupsi 2010 - , WAHIB MAHMUD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
ABSTRACT Mount Merapi is one of the most active volcano in Indonesia. The eruption occurred in 2010 led to changes in Mount Merapi ecosystem. Most of the areas in Mount Merapi are managed by Gunung Merapi National Park (GMNP) and by the community. Changing in habitat conditions and difference in management intensities will impact on bird species composition. This study aims to assess the condition of each destruction classes in birds habitat, to investigate bird species diversity in each destruction classes inside and outside the GMNP after 2010âs eruption. This research was conducted in the southern slope of Mount Merapi. Point count was used to find out bird diversity, whereas habitat condition ware obtained by Nested Sampling and Protocol Sampling. Kruskall Wallis analysis and Mann Whitney U test was used to determine differences in habitat conditions and bird species diversity. Bird habitat conditions in minor class destruction sthave an intact vegetation condition. In moderate damage class, vegetation was dominated by grasses and scrubs. In Severe damage class, pioneer scrub are often found. Different test of diversity of bird species inside and outside the GMNP show any different. Allegedly, this is caused by different management regime in each location. Different test of diversity of bird species in each destruction class inside and outside the region shows significant differences in each destruction classes. Presumably, this occurs due to the succession process after the eruption.